Genotype by environment interaction and breeding for robustness in livestock - Rauw, Wendy M.; Gomez-Raya, Luis (Frontiers in Genetics, 2015)
The increasing size of the human population is projected to result in an increase in meat consumption. However, at the same time, the dominant position of meat as the centre of meals is on the decline. Modern objections to the consumption of meat include public concerns with animal welfare in livestock production systems. Animal breeding practices have become part of the debate since it became recognized that animals in a population that have been selected for high production efficiency are more at risk for behavioural, physiological and immunological problems. As a solution, animal breeding practices need to include selection for robustness traits, which can be implemented through the use of reaction norms analysis, or though the direct inclusion of robustness traits in the breeding objective and in the selection index. This review gives a historic overview of genotype  environment interactions (the influence of the environment, reaction norms, canalization, genetic homeostasis, and phenotypic plasticity), reaction norms analysis in livestock production, options for selection for increased levels of production and against environmental sensitivity, and the direct inclusion of robustness traits in the selection index. Ethical considerations of breeding for improved animal welfare are discussed. The discussion on animal breeding practices has been initiated and is very alive today. This positive trend is part of the sustainable food production movement that aims at feeding 9.15 billion people not just in the near future but also beyond.